1994
DOI: 10.1213/00000539-199408000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from Outpatient Laparoscopic Tubal Ligation is Not Improved by Preoperative Administration of Ketorolac or Ibuprofen

Abstract: The analgesic efficacy of a single dose of ketorolac or ibuprofen given preoperatively was assessed in healthy outpatients undergoing general anesthesia for laparoscopic tubal ligation. Fifty patients were randomized to receive either ketorolac 60 mg intravenously (i.v.), ibuprofen 800 mg orally, or placebo in a double-blind manner. Anesthesia was induced with fentanyl 2 micrograms/kg, thiopental 5 mg/kg, and either vecuronium 0.1 mg/kg or succinylcholine 1.5 mg/kg i.v. and was maintained with nitrous oxide 67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…Some of these mediators evoke pain (histamine, acetylcholine and bradykinin), and others (such as prostaglandins) cause hyperalgesia, which is characterized by decreased pain threshold and increased sensitivity to supra threshold stimuli (Trombelli et al, 1996). The preoperative administration of NSAIDs may augment postoperative analgesia, as seen in the present study (95% CI, À0.61 to À0.14; 31 comparisons), chiefly by the COX-2 inhibitors class (95% CI, À0.95 to À0.33; 13 comparisons), by preventing the establishment of central sensitization in nociceptive pathways (Higgins et al, 1994;Celik et al, 2005).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Some of these mediators evoke pain (histamine, acetylcholine and bradykinin), and others (such as prostaglandins) cause hyperalgesia, which is characterized by decreased pain threshold and increased sensitivity to supra threshold stimuli (Trombelli et al, 1996). The preoperative administration of NSAIDs may augment postoperative analgesia, as seen in the present study (95% CI, À0.61 to À0.14; 31 comparisons), chiefly by the COX-2 inhibitors class (95% CI, À0.95 to À0.33; 13 comparisons), by preventing the establishment of central sensitization in nociceptive pathways (Higgins et al, 1994;Celik et al, 2005).…”
Section: Discussionsupporting
confidence: 56%
“…In the case of COX-2 inhibitors, these agents act to inhibit cyclooxygenase and reduce prostaglandin synthesis both in the spinal cord and at the periphery (McCormack, 1994) and provide analgesia by decreasing peripheral pain receptor sensitivity to mechanical stimulation and reducing tissue inflammation (Higgins et al, 1994). Injury to tissue during surgical procedures results in the release of chemical mediators of inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 , 4 7 Four other studies showed preoperative diclofenac or ketorolac to be ineffective in controlling postoperative pain. [8][9][10][11] In an attempt to clarify these results, we investigated the clinical usefulness of diclofenac 50 mg po administered one hour before day-case varicose vein repair performed under spinal anesthesia.…”
Section: Conclusion :La Prémédication Avec Le Diclofénac a Réduit Lesmentioning
confidence: 99%